Extension workers' perception of organizational climate and job satisfaction in agricultural organization in Iraq - Lafta, Ahmed Hamden; Man, Norsida; Khamees, Adnan Ibrahim; Abu Samah, Bahaman; Mohd Nawi, Nolila; Raja Yusof, Raja Nerina (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
Organizational climate and job satisfaction are known to be good and significant precursors of job performance in any organization. This is because they give the employee the stability and motivation to discharge his responsibilities efficiently. Agricultural extension employees are responsible for the provision of services and dissemination of information and knowledge to farming communities in Iraq and most other developing countries. Their perception of organizational climate and job satisfaction is poorly researched and therefore the major indicators to job performance may not be known, let alone their relationship be determined. This research work therefore looked at the perception level of these significant indicators to establish the viewpoint of the extension worker on his work environment. The sample size of 180 was taken and extension workers were blocked in the headquarters during the annual training session in the first quarter of 2016 and administered questionnaire. Data collected was analysed using descriptive statistics of percentages and frequencies. Results revealed that most of them were male (58.33 %) and have college degrees (75.00%) and are relatively young with a lot between the age of 21-30 years (75.00%) and within their first five years of employment (51.67%). The perception level for both job satisfaction and organizational climate are both at moderate level (72% and 69 %) respectively. It can be concluded that there is a great potential for the extension workers in Iraq to perform efficiently if their young age and good qualification can be leveraged on and their organizational climate condition be improved for increased motivation and job satisfaction to above moderate level.